PROBLEMS OF PREVENTION AND LEGAL COUNTERACTION TO VIOLATIONS OF PRIVACY (Journal of actual problems of jurisprudence, 2025)
This article examines the problems of preventing privacy and criminal law. The legal aspects related to the dissemination of information constituting a personal and family secret, its consequences and preventive measures are examined, the legal basis for information attacks, their consequences and ways to combat them are discussed. The effectiveness of legal mechanisms in the field of personal data protection has become the main condition for ensuring information security in society. The issues of legal regulation and legal aspects of processing in the field of confidentiality and protection of personal data, its consequences and measures aimed at preventing it are discussed. The problem of illegal dissemination of personal and family secret data is not only legal, but also social and ethical in nature. In addition to improving the legal mechanisms for solving this problem, he studied the importance of raising the information culture in society. Each citizen discussed the need to take appropriate measures to protect their personal information and insure it against illegal actions of third parties. Ensuring confidentiality in Kazakhstan is a common responsibility not only of government agencies, but also of every citizen.Keywords: privacy, personal data, information society, stalking, criminal law, morality, civil law